Executions in the United States, 1608-2002: The ESPY File - Espy, M. Watt ([Verlag nicht ermittelbar], 1988)
This collection furnishes data on executions performed under civil authority in the United States between 1608 and 2002. The dataset describes each individual executed and the circumstances surrounding the crime for which the person was convicted. Variables include age, race, name, sex, and occupation of the offender, place, jurisdiction, date, and method of execution, and the crime for which the offender was executed. Also recorded are data on whether the only evidence for the execution was official records indicating that an individual (executioner or slave owner) was compensated for an execution.